Diff Eqs 1 solutions

Diff Eqs 1 solutions -...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
Differential Equations 1 – Selection of Solutions 1c. 2 1 x e dx dy x - = Rearrange this equation: 2 x xe dx dy - = This can now be integrated directly. Integrate both sides with respect to x : dx xe y x - = 2 Make a substitution for the awkward part: let 2 x u - = dx xe y u = du du dx xe u = du x xe u - = 2 1 since x dx du 2 - = and therefore x du dx 2 1 - = du e u - = 2 1 c e u + - = 2 1 c e x + - = - 2 2 1 where c is an arbitrary constant Alternatively , the R.H.S. can be integrated in one step, but it may not be obvious. 2 x xe dx dy - = c e y x + - = - 2 2 1 where c is an arbitrary constant How do we make that last step? Recognise that in the expression dx xe x - 2 , the x in front of the 2 x e - looks like the derivative of the index, ( 29 2 x - . Instead of integrating, it might be easier to think of this in reverse – ie, what, when differentiated, gives 2 x xe - ? Differentiating x e gives x e
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Differentiating x e 2 gives x e 2 2 Differentiating 2 x e gives 2 2 x xe Differentiating 2
Background image of page 2
Image of page 3
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 04/25/2010 for the course MATH 201 taught by Professor Any during the Spring '10 term at Westminster UT.

Page1 / 6

Diff Eqs 1 solutions -...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online